Damage evolution characteristics of coal body in borehole at deep roadway wall and strength weakening mechanism of surrounding rock in borehole - Ke DING; Hualei ZHANG; Lianguo WANG; Jiaxing GUO; Yaoyao MENG (Meitan xuebao)
Coal seam drilling pressure relief technology is an important means to prevent and control rock burst disasters. Using the self-developed real-time CT scanning true triaxial loading test system, the force-strain law and internal crack propagation evolution characteristics of two different stress types models, i.e., deep coal body (three-way loading state) and shallow coal body (two-way loading state), under different borehole diameters were studied. The pre-peak crack damage relationship of deep and shallow boreholes in the roadway was established, and the strength weakening mechanism of surrounding rock of pressure relief boreholes in deep roadway was revealed. The results show that compared with the undrilled samples, the coal samples with different stress types are affected by the stress environment and the borehole diameter. With the drilling and the increase of the borehole diameter, the stress drop phenomenon of the deep coal samples in the roadway wall disappears after the peak stress, which is beneficial to reduce the sudden release of the energy of the samples, while the shallow coal samples in the roadway wall cannot eliminate the stress drop phenomenon. In terms of internal crack propagation, the cracks in the deep coal samples of the roadway wall are less developed, and the cracks are developed at a certain angle, while the cracks in the shallow coal samples of the roadway wall are almost vertically developed. With the increase of borehole diameter, the number of cracks in the deep and shallow coal samples of the roadway wall increases to a certain extent, but the number of cracks in the shallow coal samples of the roadway wall is more, and the sealing of the coal powder in the borehole is more obvious. The change of borehole and aperture has a greater impact on the shallow coal samples of the roadway wall. Under the same drilling conditions, the shallow coal body of the roadway wall is more likely to be destroyed and cannot play the effect of pressure relief and disaster reduction. Based on the difference between the deep and shallow drilling coal bodies of the roadway wall, the function expressions of the crack damage variables of the deep and shallow coal bodies of the roadway wall under different drilling apertures are established. The weakening mechanism of surrounding rock strength of deep roadway pressure relief drilling is revealed, and the concept and method of deep roadway reaming and pressure relief are proposed.